Development and Validation of a Self-Determination Theory-Based Measure of Motivation to Exercise and Diet in Children - Pietrabissa, Giada; Rossi, Alessandro; Borrello, Maria; Manzoni, Gian Mauro; Mannarini, Stefania; Castelnuovo, Gianluca; Molinari, Enrico (Frontiers in Psychology, 2020)
Objective: to develop and test the factorial structure of a new self-determination theory-based measure of behavioral regulation in children. Method: 590 (F = 51.7%) children aged 7-11 years completed the Motivation to Exercise and Diet (MED-C) questionnaire, which comprises 16 items (8 for exercise and 8 for diet) grouped into eight-factors (5 motivations and 3 needs). Psychometric testing included confirmatory factor analysis and internal consistency. Measurement invariance analyses were also performed to evaluate whether the factorial structure of the MED-C was equivalent for gender (male vs. female), age (< 9yo vs. > 10yo) and the perception of having at least one parent with overweight or obesity (yes vs. no). Results: factorial analysis confirmed an acceptable factors solution for the MED-C and a good fit to the data for both the exercise and the diet subscales assessed independently. The Maximal Reliability coefficient revealed good reliability for the exercise and the diet subscales. Moreover, the MED-C factor structure was invariant across group comparisons. Discussion: findings support the construct validity and reliability of the MED-C. Therefore, it represents the first validated instrument simultaneously measuring motivational regulation and psychological need satisfaction in the context of children’s exercise and diet. Considering the goodness of these results, scale percentile ranks of the total score distribution as well as the z-score and the T-score were provided for clinical and research purposes. Conclusion: The MED-C might support the understanding of motivations and needs of children with weight problems and assist their process of behavioural change in primary and secondary prevention programs. Psychological factors represent, in fact, potential targets for interventions to increase children’s motivation to exercise and diet.